Divergences in subarctic-alpine plant phenology and reproductive success due to snowmelt timing - Liu, Che (Helsingfors universitet, 2016)
Snowmelt timing has been proven critical to the phenology in subarctic and alpine ecosystems. Nevertheless, its impacts on the phenology of dwarf-shrub-dominated vegetation on high-latitudinal Fennoscandian fells are not yet sufficiently studied. This project focusses on the divergences in phenological timings and reproductive success caused by naturally different snowmelt timings in this area. The study site was on fell Saana in northwest Finland. The data was collected from a site covering three snowmelt timings located in two aspects (fully factorial, 4 replicates) from 20th of May to 4th of September, 2015, totalling 108 days. The phenological events (e.g. leaf unfolding, anthesis, and leaf colouring) of 12 species of three growth forms (dwarf shrub, forb, and graminoid) were recorded. The statistical analyses show that different snowmelt timings result in significant differences in the time points (expressed in day of year, DOY) of peak flowering and shoot elongation, as well as the green-leaved durations (days); however, flowering duration is rather constant across snowmelt timings. Significant differences are also found in the reproductive success of several species. The results suggest that in subarctic-alpine vegetation, an earlier snowmelt timing 1) elongates the duration of vegetative growth, 2) advances the timing of peak flowering while the flowering duration remains unchanged, and 3) potentially impedes reproductive success in some species, but generally the pattern is heterogeneous. Thus, snowmelt timing is causing divergences among the phenological traits and potentially within the reproductive success of dwarf shrub species in this area. In the long term, these phenomena may impact the local biodiversity and biochemical cycles, which may be a long-term effect of the shifting snowmelt timing due to global change.